Fluorimetric identification of sulfonamides by carbon dots embedded photonic crystal molecularly imprinted sensor array. (1st May 2023) - Zhang, Shishun; Shao, Keman; Hong, Chengyi; Chen, Suyan; Lin, Zhengzhong; Huang, Zhiyong; Lai, Zhuzhi
Highlights: Novel fluorescence array was developed for sulfonamides discrimination. The sensor array exhibited rapid response for sulfonamides. Sulfonamides could be discriminated by pattern recognition. Linear discriminant analysis gave 100% identification accuracy in mixed analytes. The sensor arrays were used to identify-five sulfonamides spiked in fish samples. Abstract: Identification of sulfonamides (SAs) residues in food is vital for human health. A set of 4-channel sensor array was constructed by carbon dots (CDs) embedded in photonic crystal molecularly imprinted (PCMIP@CDs) film which included 3 PCMIP@CDs units and 1 PCNIP@CDs unit to determine typical SAs: sulfadimethoxine, sulfathiazole, sulfaguanidine, sulfamethazine, sulfadiazine. Under the optimal conditions, the response time of the sensor array was only 200 s. Moreover, 300 fluorescence response signals (4 sensor units × 5 sulfonamides × 3 concentrations × 5 repeats) were processed by pattern recognition technique to analyze the ability of the sensor array to recognize 5 kinds of SAs. Subsequently, the linear discrimination analysis (LDA) method was used to identify the five SAs simultaneously with 100 % classification accuracy and the limit of detection was 0.01–0.26 nmol/L. Moreover, the proposed method can effectively identify-five SAs in water and fish samples.